Higher in-hospital proportion of breast milk intake improves brain functional connectivity and neurological assessment in preterm infants - Yang, Rui; Wang, Hua; Cai, Qian; Chen, Danqi; Zhu, Jiajun; Yuan, Shuiqin; Wang, Fang; Xu, Xinfen (Frontiers in Pediatrics, 2025)
ObjectivePreterm infants may face neurodevelopmental challenges linked to altered brain maturation processes. This study aimed to investigate the impact of in-hospital breast milk intake on brain resting-state functional connectivity (rs-FC) and neurological assessment at discharge in preterm infants.MethodsWe collected data on breast milk intake from 97 preterm infants, evaluated neurological outcomes using the Amiel-Tison Neurological Assessment (ATNAT), and assessed rs-FC via functional near-infrared spectroscopy (fNIRS). Groups were stratified by breast milk intake proportion (cutoffs of >70% vs. ≤70%; cutoffs of >90% vs. ≤90%), and conducted logistic regression analysis to explore the relationship between rs-FC and neurological assessment.ResultsPreterm infants with >70% breast milk intake exhibited significantly higher ATNAT levels (χ2=8.306,p = 0.004) and stronger rs-FC (p = 0.001) between the right precentral gyrus (PCG) and inferior parietal lobe (IPL). The >90% intake group also showed higher ATNAT levels (χ2=7.090,p = 0.008) and further rs-FC enhancements (PCG-PFL: p = 0.016; PCG-IPL: p = 0.008). Logistic regression confirmed rs-FC as a predictor of optimal neurological assessment [p = 0.011, Exp (B) = 0.206, 95% CI: 0.062– 0.682].ConclusionHigher in-hospital breast milk intake (>70% of total enteral nutrition) improves rs-FC and neurological outcomes in preterm infants, with dose-dependent effects.